Effect Of Foot Reflexology Therapy On Fatigue And Sleep Quality In Children Undergoing Hemodialysis: A Systematic Review - Purnamawati, IGA Dewi Purnamawati; Sukyati, Ira; Simanjuntak, Merida (Sean Institute, 2023)
Background: Children with chronic kidney failure often experience fatigue and lack of sleep which has an impact on the child's quality of life, so intervention is needed to overcome these problems. Object: This study aims to determine the impact of foot reflexology therapy on fatigue and sleep quality in children with chronic kidney failure who are undergoing hemodialysis. Method: In this research, we identified findings on the research topic. The data used is secondary data taken from scientific articles in Indonesian and English from 2016 to 2022. Literature searches were carried out comprehensively through electronic databases, from Elsevier, Pubmed (NCBI), ResearchGate, Cochrane Library and Google Scholar. Results: from 4 articles, foot reflexology therapy can reduce fatigue and improve the sleep quality of children undergoing hemodialysis. Conclusion: This study shows that foot reflexology therapy can reduce fatigue and improve sleep quality in patients undergoing hemodialysis. Recommended that foot reflexology therapy be used to reduce fatigue and sleep disorders in children undergoing hemodialysis.